Safe Motherhood Practices in Panch Pokhari Thangpal Rural Municipality, Nepal - Pasa, Rajan Binayek; Giri, Sunita; Nabita, Dani (Research Nepal Journal of Development Studies, 2020)
This paper highlights on safe motherhood practices in a rural municipality in Nepal. Primary data are collected through the survey questionnaire from 196 respondents who are married women of reproductive age group. The findings show that knowledge and practices on safe motherhood practices are moderately satisfied. The majority of the delivery cases are being handled in the health posts at a prolonged labor stage with the support of their husbands. The cord-cutting practice is also becoming scientific with the use of using sterilized scissors. Mothers are happily practicing the breastfeeding culture at least for two to three years after delivery. However, the rural mothers are facing problems such as vomiting, bleeding, anemia swelling of the leg, back aching, and head aching during pregnant periods, possibly due to the traditional treatment practices and the local food habits. Majorities of the respondents have good knowledge of contraceptives devices, but they prefer to report on health posts only for a postnatal checkup. All in all, safe motherhood practices in the rural community are found moderately adequate and needed to be improved by offering antenatal, natal, and postnatal services at no cost.